Inovasi Produk Olahan Susu Aneka Rasa dan Warna di Desa Pagersari Kecamatan Ngantang Kabupaten Malang - Faizin, Nur; Irawati, Santi; Soseco, Thomas; Nurjanah, Nunung (LPPM Universitas Flores, 2023)
This paper presents the results of a community engagement project conducted in Pagersari village, Ngantang district. The project aimed to address issues related to milk processing, packaging, and marketing in the community. The proposed solution involved the development of flavoured and coloured milk beverages that could be produced at home using simple cooking utensils. The community learned how to transform milk into products with various appealing flavours and colours through training and mentoring. Additionally, packaging and labelling training was provided to enhance the products' visual appeal. Marketing efforts included the provision of attractive stands and carts with character designs for selling milk products. Collaboration with the State University of Malang was established to optimize processing and marketing as the project expanded. Ongoing monitoring and evaluation, broadening offline and online marketing channels, and strengthening collaborations with relevant stakeholders were recommended for further improvement. This project is expected to sustainably impact the Pagersari community and serve as an inspiring model for home-based industry development in other regions